Management of the Literacy Movement Program (LMP) to Improve Reading Culture in Elementary Schools - Indra Prasetia; Muhammad Adlan (Journal of Innovation in Educational and Cultural Research, 2022)
This study aims to analyze the planning, implementation, and evaluation of the elementary school literacy program in the city of Binjai. The method in this research is descriptive with a qualitative approach. The subjects of this study were principals, teachers, students, and parents of students. The results of the study indicate that planning is done by compiling a program by a team formed by the school. The implementation of the program is carried out with mandatory school library visits, reading books in class, developing literacy creativity, and student literacy work. While the evaluation is carried out to measure the achievement of the results of the literacy program run by the school. The conclusion from the results of this study is that the management of literacy program planning is carried out through a subject teacher discussion forum, planned annually based on the school's annual work program plan. The literacy program activity is an integration of listening, speaking, writing, reading, and critical thinking skills. In addition, the literacy program implemented has improved the reading culture among teachers and students, especially in superior and independent schools. The literacy program at Binjai Elementary School is carried out through three stages, namely the habituation, development, and learning stages. At the evaluation level, it is carried out in a programmed, measurable manner and is held every semester. In general, the literacy program is very good and effective because it can increase students' literacy interests and competencies, also increase school library learning resources, improve literacy culture and student character.